2019
DOI: 10.1039/c9an01884k
|View full text |Cite
|
Sign up to set email alerts
|

A simple hypochlorous acid signaling probe based on resorufin carbonodithioate and its biological application

Abstract: A novel HOCl signaling probe based on the oxidative hydrolysis of resorufin carbonodithioate to generate resorufin dye was investigated and applied to cell imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
1
7
0
4
Order By: Relevance
“…While thiol-based probes have demonstrated their ability to detect Hg 2+ , 45,46 their sensitivity to interference from Hg 2+ has not been a major concern in most biological applications due to the typically low concentrations of these metal ions. 47,48 We additionally confirmed that the Myco-OCl probe interacts with the thiophilic metal ion Hg 2+ displaying a low fluorescence signal (Fig. 1).…”
Section: Uv-visible and Fluorescence Studysupporting
confidence: 62%
“…While thiol-based probes have demonstrated their ability to detect Hg 2+ , 45,46 their sensitivity to interference from Hg 2+ has not been a major concern in most biological applications due to the typically low concentrations of these metal ions. 47,48 We additionally confirmed that the Myco-OCl probe interacts with the thiophilic metal ion Hg 2+ displaying a low fluorescence signal (Fig. 1).…”
Section: Uv-visible and Fluorescence Studysupporting
confidence: 62%
“…Thus, among the trends in the development and application of small-molecule probes for detecting HOCl, one can note the frequent use of DAMN as a target for HOCl in sensors, for example, in CSN [63], RO610 [78], compound (VIII) [90], and HQMN [91]. A new branch was the use of probes based on phenoxazine (CB [70], RT-1 [73], BR-O [74], BR-1 [75], BC-2, and BC-3 [77]), as well as a hybrid fluorophore rhodol (RO610 [78], HKOCl-4, and its derivatives [79]). Of interest is the strategy of simultaneous registration of several types of oxidants, implemented, for example, in the work of Zhang et al [67] using the FHZ probe as an example.…”
Section: Discussionmentioning
confidence: 99%
“…(d) For kinetic studies of HOCl formation (reaction time <1 min), all probes other than BCO and BETC (reaction time not determined) [62], FN-1 and FN-2 [69], RT-1 [73], BR-O [74], BR-1 [75], Dcp-EPtz [88], EtS-DMAB [92], NSSN [93].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations